2017
DOI: 10.1016/j.adaj.2017.09.011
|View full text |Cite|
|
Sign up to set email alerts
|

Dental disease before radiotherapy in patients with head and neck cancer

Abstract: Background No evidence-based guidelines exist for preventive dental care before radiation therapy (RT) in head and neck cancer (HNC) patients. An ongoing multicenter, prospective cohort study, Clinical Registry of Dental Outcomes in Head and Neck Cancer Patients (OraRad) (1U01DE022939-01), is addressing this knowledge gap. The present manuscript evaluates the level of pre-RT dental disease in the OraRad cohort, factors associated with dental disease, and dental treatment recommendations made pre-RT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Radiation therapy has a site-specific effect, whereas chemotherapy has a systemic effect. These two latter modalities cause disturbances in the integrity and function of the oral cavity because they are not able to destroy tumor cells without causing damage or death to normal cells [1,3,4,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation therapy has a site-specific effect, whereas chemotherapy has a systemic effect. These two latter modalities cause disturbances in the integrity and function of the oral cavity because they are not able to destroy tumor cells without causing damage or death to normal cells [1,3,4,11].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the complications resulting from cancer treatments, discomfort and pain may be responsible for causing a nutritional deficit, altered immune response and a longer hospital stay, and may even trigger a sepsis and expose the patient to a greater risk of life. However, oral alterations can be minimized with the support of the multidisciplinary team and commitment of the dental surgeon in the clinical management of the patient in cancer treatment [1][2][3]17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would ensure that measurements can be carried out, with or without metallic fillings, without major modifications of the phantom. The phantom should be usable for various issues related to the dose distribution of external beam radiotherapy, brachytherapy and stereotactic radiotherapy (13)(14)(15)(16)(17)(18). Moreover, it should be usable for magnetic resonance (MR)-imaging.…”
Section: Methodsmentioning
confidence: 99%
“…The dental surgeon must diagnose and treat the RT acute oral toxicities 24 (OM [25][26][27] , dysgeusia, 12,22,28,29 infections, pain, and xerostomia) (Table 3), that implicate an inability to eat, speak, clean, increased costs with hospitalization, and reduced quality of life. [30][31][32][33] Nutritional care, constant water intake, and use of salivary substitutes are recommended 12,93 In a recent study, the use of zinc-L-carnosine demonstrated encouraging results in the treatment of dysgeusia in these patients 94…”
Section: Prosthetic Treatmentmentioning
confidence: 99%